PETROLEUM GEOCHEMISTRY STUDY AND MODELLING OF X BLOCK, SOUTH SUMATRA BASIN - PURNAMASARI (NIM: 22014007), ELLA
South Sumatra Basin is Tertiary back-arc basin which the formation is caused by the interaction of Sunda shelf and Hindia Oceanic Crust. There are some debatable arguments among previous researchers about its potential source rock. Therefore it becomes an interesting topic to be studied further by doing geochemistry analysis around the area. The study has been done in X Blok area and involve all formations. This study used 174 samples comprises of source rock and crude oil samples. Source rock characterization is based on the analysis of richness, quality, maturity from the source rock organic content. Crude oil characterization is based on gas chromatograph and gas chromatograph-mass spectometry analyse. Correlation between source rock and crude oil has been used to unreveal the relationship in between those two matters. Migration pathway to shown by 2D basin modelling on the study area. Source rock from Lemat Formation and Talangakar Formation is rich of organic content and having kerogen type II-III/II. Regarding to vitrinite reflectance of the organic content, those two formations are not mature yet. There are two source rock facies, which are marine/transition facies and shallow lacustrine facies. Moreover there are two crude oil families, they are crude oil family 1 that is dominated by continental organic content with few algae existency and crude oil family 2 that is dominated by mixed of continenal and algae organic contents. Corelations of the crude oil to the source rock is in negative correlation. Thus it assumed that the crude oil is possibly coming from other source rock outside the area of study. According to the 2D basin modelling, migration pathway is dominated by vertical flow or in other word, the oil is moved up from the older to the youngest formation. However there is still a possibility that the hidrocarbon migrated through a big fault which passes through another shallower source rock interval. Direction of migration from 2D basin modelling just explained condition around SID-01 well. The source of hydrocarbon is interpreted moving from outside blockÃ‚Â’s basin which then migrated to the positive structure around the study area.